The Role of GMP Audits in Ensuring Drug Quality and Safety in Drugs - Dandekar, Mayur; khobragade, Deepak; Salve, Yash; Mandhane, Sakshi; Mirzapure, Isha (International Journal of Pharmaceutical Investigation, 2026)
The importance of GMP audits in ensuring the quality, safety, and efficacy of pharmaceuticals is unmistakable. These audits are systematic appraisals of facilities, processes, personnel, documentation, and quality management systems that assure compliance with regulatory standards both nationally and internationally. The agencies that govern the regulatory framework for GMP compliance auditing are the US Food and Drug Administration (FDA), the European Medicines Agency (EMA), the World Health Organization (WHO), and the Pharmaceutical Inspection Co-operation Scheme (PIC/S). Key aspects of GMP auditing include quality management systems, facility and equipment maintenance, training for personnel, raw material control, process validation, laboratory testing, and documents. Unfortunately, several of those have affected the effectiveness of GMP auditing. They include inconsistency in global regulations, resource constraints, a continuously changing cloud of expectations regarding compliance, data integrity issues, and complexities found in the supply chain. The pharmaceutical sector is increasingly relying on the benefits of adopting digital technologies like Artificial Intelligence (AI), blockchain, and predictive analytics to improve audit processing efficiency and transparency in real-time monitoring of compliance. The future of GMP audits will be driven by automation, regulated harmonization, virtual inspection, and sustainable manufacturing practices to ensure proactive risk management. The strength of GMP audits is necessary for the realization of pharmaceutical quality, thus protecting public health from a continuously changing regulatory environment.
Keywords: GMP audits; Pharmaceutical quality; Drug safety; Regulatory compliance; Quality management system; AI; Predictive compliance; Pharmaceutical manufacturing.